2015
DOI: 10.1186/s12912-015-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision in primary health care; experiences of district nurses as clinical supervisors - a qualitative study

Abstract: BackgroundLearning in the clinical environment is an important part of nursing education. Several recent studies focusing on clinical learning have been based on hospital settings. Little is known about primary health care (PHC) as clinical environment where district nurses (DNs) or nurses supervise students. It is important to understand more about opportunities and difficulties in supervising in this area in order to develop PHC as an optimal learning environment for nursing students. The main objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…The third category, 'creating a reciprocal relationship with the student', was supported by five findings. Nurses explained that their role as a mentor is not only important for creating a reciprocal and mutual relationship with students (Bos et al, 2015;Carlson et al, 2009b;Hilli et al, 2014b;Jokelainen et al, 2013b), but also for mutual respect with other stakeholders, i.e. patients, management, and fellow staff members (Hilli et al, 2014b;Jokelainen et al, 2013b).…”
Section: Creating An Interactive Relationship With the Studentmentioning
confidence: 99%
See 1 more Smart Citation
“…The third category, 'creating a reciprocal relationship with the student', was supported by five findings. Nurses explained that their role as a mentor is not only important for creating a reciprocal and mutual relationship with students (Bos et al, 2015;Carlson et al, 2009b;Hilli et al, 2014b;Jokelainen et al, 2013b), but also for mutual respect with other stakeholders, i.e. patients, management, and fellow staff members (Hilli et al, 2014b;Jokelainen et al, 2013b).…”
Section: Creating An Interactive Relationship With the Studentmentioning
confidence: 99%
“…The fourth category, 'able to J o u r n a l P r e -p r o o f reflect during mentoring', was supported by five findings. In general, mentors grasped the importance of reflection and discussion with students during clinical practice (Bos et al, 2015;Carlson ym., 2009;Hilli et al, 2014a;Landmark et al 2003;Jokelainen et al, 2013b).…”
Section: Creating An Interactive Relationship With the Studentmentioning
confidence: 99%
“…Students` supervision in nursing clinical studies is through the peer study model and/or one-to one style of supervision [20]. An alternative study model called peer study model is developed [20], since the traditional one to one style of supervision seem impossible to realize as continues changes in health services become more extensive in the clinical areas and less numbers of nurse mentors make students` supervision difficult to meet. The peer study model means that two students go together, guide, support and assess each other in the learning process.…”
Section: Assessment Of Students In Practicementioning
confidence: 99%
“…The peer study model means that two students go together, guide, support and assess each other in the learning process. However, nurse mentor in practice is the one that has "control" with both students [20]. As mentioned before, assessment is a core element of supervision [6].…”
Section: Assessment Of Students In Practicementioning
confidence: 99%
“…One way of improving this may be to encourage newlyqualified nurses to consider it as a career, and a Swedish study recently sought to understand the experiences of DNs who act as supervisors to undergraduate nursing students. 2 Data from six focus groups demonstrated that, although participants felt proud to be DNs and were keen to share the holistic approach and ongoing care they can offer, they also felt abandoned by their managers, colleagues, and fellow nurse teachers at the universities. The authors suggest improving social support, and communication between DN supervisors should be a priority at both university and practice level.…”
mentioning
confidence: 99%